2018
DOI: 10.1098/rstb.2016.0445
|View full text |Cite
|
Sign up to set email alerts
|

The rate of telomere loss is related to maximum lifespan in birds

Abstract: Telomeres are highly conserved regions of DNA that protect the ends of linear chromosomes. The loss of telomeres can signal an irreversible change to a cell's state, including cellular senescence. Senescent cells no longer divide and can damage nearby healthy cells, thus potentially placing them at the crossroads of cancer and ageing. While the epidemiology, cellular and molecular biology of telomeres are well studied, a newer field exploring telomere biology in the context of ecology and evolution is just eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
177
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 121 publications
(190 citation statements)
references
References 75 publications
(129 reference statements)
8
177
1
Order By: Relevance
“…Similar age-related telomere length sex differences were also found in water pythons and other vertebrates (Barrett & Richardson, 2011;Jemielity et al, 2007;Ujvari & Madsen, 2009), indicating a relationship between high mortality and telomere maintenance in somatic cells resulting in shorter life span (Hornsby, 2007;Kirkwood, 1977;Tricola et al, 2018). Similar age-related telomere length sex differences were also found in water pythons and other vertebrates (Barrett & Richardson, 2011;Jemielity et al, 2007;Ujvari & Madsen, 2009), indicating a relationship between high mortality and telomere maintenance in somatic cells resulting in shorter life span (Hornsby, 2007;Kirkwood, 1977;Tricola et al, 2018).…”
Section: Discussionsupporting
confidence: 61%
“…Similar age-related telomere length sex differences were also found in water pythons and other vertebrates (Barrett & Richardson, 2011;Jemielity et al, 2007;Ujvari & Madsen, 2009), indicating a relationship between high mortality and telomere maintenance in somatic cells resulting in shorter life span (Hornsby, 2007;Kirkwood, 1977;Tricola et al, 2018). Similar age-related telomere length sex differences were also found in water pythons and other vertebrates (Barrett & Richardson, 2011;Jemielity et al, 2007;Ujvari & Madsen, 2009), indicating a relationship between high mortality and telomere maintenance in somatic cells resulting in shorter life span (Hornsby, 2007;Kirkwood, 1977;Tricola et al, 2018).…”
Section: Discussionsupporting
confidence: 61%
“…Two papers in this issue harness these emerging data on avian telomeres to provide important new insights into the relationship between telomere length and longevity. Tricola et al [19] compare average telomere length and rates of change in telomere length with age across 19 species of birds. They show that species with longer maximum lifespans have slower rates of telomere loss with age than species with shorter lifespans.…”
Section: Is Telomere Length or Loss Predictive Of Longevity?mentioning
confidence: 99%
“…But longitudinal studies are difficult, especially in long-lived species. The comparative analysis of Tricola et al [19] and the meta-analysis of Wilbourn et al [20] are both limited to using cross-sectional data. For this reason, their conclusions regarding the importance of initial telomere length, and the rate of telomere loss over different time scales, for lifespan remain tentative.…”
Section: Future Researchmentioning
confidence: 99%
“…that, in general, older individuals have shorter telomeres than younger ones with the greatest loss in telomeres occurring early in life (Heidinger et al, 2012;Pauliny, Larsson, & Blomqvist, 2012;Salomons et al, 2009;Spurgin et al, 2018;Tricola et al, 2018).…”
Section: Both Longitudinal and Cross-sectional Studies In Birds Showmentioning
confidence: 99%
“…In mammals, a comparative study found that short-lived, small species have longer telomeres and higher telomerase expression than long-lived, large species (Gomes et al, 2011). In birds, absolute telomere length does not seem to relate to variation in lifespan between species; however, longer-lived avian species seem to have lower rates of telomere shortening than shorter-lived species (Dantzer & Fletcher, 2015;Haussmann et al, 2003;Sudyka, Arct, Drobniak, Gustafsson, & Cichoan, 2016;Tricola et al, 2018). In birds, absolute telomere length does not seem to relate to variation in lifespan between species; however, longer-lived avian species seem to have lower rates of telomere shortening than shorter-lived species (Dantzer & Fletcher, 2015;Haussmann et al, 2003;Sudyka, Arct, Drobniak, Gustafsson, & Cichoan, 2016;Tricola et al, 2018).…”
Section: Both Longitudinal and Cross-sectional Studies In Birds Showmentioning
confidence: 99%